A novel and smart automatic light-seeking flowerpot for monitoring flower growth environment - Zhang, Xihai; Liu, Dong; Fan, Chengguo; Du, Jiali; Meng, Fanfeng; Fang, Junlong (International Journal of Agricultural and Biological Engineering, 2018)
Although the flowerpot is widely used for indoor flowers, it cannot meet the needs of intelligent management during the uncared-for period. The objective of this study was to design a new microcontroller-based smart flowerpot. Its overall system was composed of three parts: information collection layer, automatic control layer and data transmission layer. Firstly, in the process of collecting information, the Laiyite criterion and the normalized weighted average algorithm were adopted to improve the accuracy of information collection. Secondly, for making precise control decisions, the fuzzy control was used to achieve automatic on-demand watering. Finally, the method for comparative analysis of regional light intensity was utilized to achieve light-seeking and light-supplementing. Experimental results showed that the smart flowerpot had strong anti-jamming performance for information collection, the relative soil moisture of flowers could be stably maintained near the optimum humidity (65%), and the light was well-distributed on the flower with the error angle of light-supplementing ranged from –3° to 3°. Keywords: smart flowerpot, automatic watering, seeking light, supplementing light control, microcontroller DOI: 10.25165/j.ijabe.20181102.2786 Citation: Zhang X H, Liu D, Fan C G, Du J L, Meng F F, Fang J L. A novel and smart automatic light-seeking flowerpot for monitoring flower growth environment. Int J Agric & Biol Eng, 2018; 11(2): 184–189.